Micro-computed tomography analysis of void volume in sealer layer placed using Vibrospiral novel instrument: an in vitro study - Banerjee, Avishikta; Hegde, Mithra Nidarsh; Shenoy, Kalyanpur Rajat (Frontiers in Dental Medicine, 2025)
AimEndodontic sealers form an intermediary layer between the solid canal filling material, like gutta-percha, and the dentinal wall to fill the voids and porosities between them and establish a fluid-impervious seal, which is essential to prevent reinfection of the canal system. Sealer placement instruments are used to carry and coat the sealer on the walls of the fine, tortuous root canal system. The Vibrospiral is a piezoelectrically activated novel sealer coating instrument that has been designed to place a thin, uniform, void-free sealer layer by its vibratory motion. This study compared the void volume percentage in the sealer layer when placed with the Vibrospiral and two other conventional coating instruments.MethodologyA total of 36 caries-free natural mandibular premolars were disinfected, decoronated, and biomechanically prepared. They were randomly assigned to one of the three groups (n = 12) based on the mode of sealer application: group 1=K-file, group 2=Lentulo spiral, and group 3=Vibrospiral. After sealer placement, the canals were obturated with gutta-percha and the sealer was allowed to set. Samples were then subjected to micro-computed tomography (micro-CT) to assess the void volume. The data acquired were statistically analysed using ANOVA and the Tukey test, and the significance level was set at <0.05.ResultsThe findings revealed that the Vibrospiral placed sealer layers with the least void volume percentage overall (3.5%), followed by Lentulo spiral (19.21%) and K-file (22.01%).ConclusionsThe piezoelectrically activated novel sealer placing instrument, the Vibrospiral, has promising potential in effectively placing a relatively non-voided sealer layer.